2001
DOI: 10.1002/cne.1351
|View full text |Cite
|
Sign up to set email alerts
|

Activity and localization of 3β‐hydroxysteroid dehydrogenase/ Δ5‐Δ4‐isomerase in the zebrafish central nervous system

Abstract: Little information is available for neurosteroidogenesis in the central nervous system (CNS) of lower vertebrates. Therefore, in the present study, we examined the enzymatic activity and localization of 3beta-hydroxysteroid dehydrogenase/Delta5-Delta4-isomerase (3betaHSD), a key steroidogenic enzyme, in the CNS of adult male zebrafish to clarify central progesterone biosynthesis. Biochemical studies together with HPLC analysis revealed that the zebrafish brain converted pregnenolone to progesterone, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 66 publications
6
81
0
Order By: Relevance
“…Interestingly, in vitro studies using cultured cerebellar slices of newborn rats showed that progesterone promotes dendritic growth of the Purkinje neuron (Sakamoto et al, 2001b). A similar result was obtained by in vivo studies.…”
Section: Nongenomic Action Of Pregnenolone Sulfatesupporting
confidence: 73%
See 3 more Smart Citations
“…Interestingly, in vitro studies using cultured cerebellar slices of newborn rats showed that progesterone promotes dendritic growth of the Purkinje neuron (Sakamoto et al, 2001b). A similar result was obtained by in vivo studies.…”
Section: Nongenomic Action Of Pregnenolone Sulfatesupporting
confidence: 73%
“…A similar result was obtained by in vivo studies. Electron microscopic analysis further revealed that progesterone induces an increase of the density of synapses on the Purkinje neuron (Sakamoto et al, 2001b). Furthermore, intranuclear receptors for progesterone were expressed in the Purkinje neuron (Sakamoto et al, 2001b).…”
Section: Nongenomic Action Of Pregnenolone Sulfatementioning
confidence: 91%
See 2 more Smart Citations
“…The Purkinje cell is a major site for the formation of neurosteroids including estradiol in rats and other vertebrates (Usui et al, 1995;Ukena et al, 1998Ukena et al, , 1999Takase et al, 1999;Matsunaga et al, 2001;Sakamoto et al, 2001bSakamoto et al, , 2003aMatsunaga et al, 2004). We found previously that estradiol promotes dendritic growth of Purkinje cells in newborn rats and show now that this result generalizes to newborn mice.…”
Section: Discussionmentioning
confidence: 58%